Binding N2, N2H2, N2H4, and NH3 to transition-metal sulfur sites: modeling potential intermediates of biological N2 fixation. - Heinemann, Frank Wilhelm; et al. (Chemistry - A European Journal, 2004)
In the quest for low-molecular-weight metal sulfur complexes that bind nitrogenase-relevant small molecules and can serve as model complexes for nitrogenase, compounds with the [Ru(PiPr(3))('N(2)Me(2)S(2)')] fragment were found ('N(2)Me(2)S(2)'(2-)=1,2-ethanediamine-N,N'-dimethyl-N,N'-bis(2-benzenethiolate)(2-)). This fragment enabled the synthesis of a first series of chiral metal sulfur complexes, [Ru(L)(PiPr(3))('N(2)Me(2)S(2)')] with L=N(2), N(2)H(2), N(2)H(4), and NH(3), that meet the biological constraint of forming under mild conditions. The reaction of [Ru(NCCH(3))(PiPr(3))('N(2)Me(2)S(2)')] (1) with NH(3) gave the ammonia complex [Ru(NH(3))(PiPr(3))('N(2)Me(2)S(2)')] (4), which readily exchanged NH(3) for N(2) to yield the mononuclear dinitrogen complex [Ru(N(2))(PiPr(3))('N(2)Me(2)S(2)')] (2) in almost quantitative yield. Complex 2, obtained by this new efficient synthesis, was the starting material for the synthesis of dinuclear (R,R)- and (S,S)-[micro-N(2)[Ru(PiPr(3))('N(2)Me(2)S(2)')](2)] ((R,R)-/(S,S)-3). (Both 2 and 3 have been reported previously.) The as-yet inexplicable behavior of complex 3 to form also the R,S isomer in solution has been revealed by DFT calculations and (2)D NMR spectroscopy studies. The reaction of 1 or 2 with anhydrous hydrazine yielded the hydrazine complex [Ru(N(2)H(4))(PiPr(3))('N(2)Me(2)S(2)')] (6), which is a highly reactive intermediate. Disproportionation of 6 resulted in the formation of mononuclear diazene complexes, the ammonia complex 4, and finally the dinuclear diazene complex [micro-N(2)H(2)[Ru(PiPr(3))('N(2)Me(2)S(2)')](2)] (5). Dinuclear complex 5 could also be obtained directly in an independent synthesis from 1 and N(2)H(2), which was generated in situ by acidolysis of K(2)N(2)(CO(2))(2). Treatment of 6 with CH(2)Cl(2), however, formed a chloromethylated diazene species [[Ru(PiPr(3))('N(2)Me(2)S(2)')]-micro-N(2)H(2)[Ru(Cl)('N(2)Me(2)S(2)CH(2)Cl')]] (9) ('N(2)Me(2)S(2)CH(2)Cl'(2-) =1,2-ethanediamine-N,N'-dimethyl-N-(2-benzenethiolate)(1-)-N'-(2-benzenechloromethylthioether)(1-)]. The molecular structures of 4, 5, and 9 were determined by X-ray crystal structure analysis, and the labile N(2)H(4) complex 6 was characterized by NMR spectroscopy.